Multiferroicity of Carbon‐Based Charge‐Transfer Magnets. (11th November 2014) - Qin, Wei; Gong, Maogang; Chen, Xiaomin; Shastry, Tejas A.; Sakidja, Ridwan; Yuan, Guoliang; Hersam, Mark C.; Wuttig, Manfred; Ren, Shenqiang
<x xml:space="preserve">Abstract</x> A new type of carbon charge‐transfer magnet, consisting of a fullerene acceptor and single‐walled carbon nanotube donor, is demonstrated, which exhibits room temperature ferromagnetism and magnetoelectric (ME) coupling. In addition, external stimuli (electric/magnetic/elastic field) and the concentration of a nanocarbon complex enable the tunabilities of the magnetization and ME coupling due to the control of the charge transfer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>